Différences entre les versions de « Espace préhilbertien réel/Exercices/Polynômes de Legendre »

+
(+)
(+)
Par récurrence, il vient :
:<math>\int_{-1}^{1} \frac{\mathrm d^n}{\mathrm dx^n}((x^2-1)^n) \frac{\mathrm d^p}{\mathrm dx^p}((x^2-1)^p)\mathrm dx = (-1)^p \int_{-1}^{1} (x^2-1)^p\frac{\mathrm d^{n+p}}{\mathrm dx^{n+p}}((x^2-1)^n) \mathrm dx</math>.
*Si <math>n=p</math>, il vient :
:<math>(-1)^n \int_{-1}^{1} (x^2-1)^n\frac{\mathrm d^{2n}}{\mathrm dx^{2n}}((x^2-1)^n) \mathrm dx = (-1)^n (2n)! \int_{-1}^{1} (x^2-1)^n \mathrm dx = (-1)^n (2n)! \int_{-1}^{1} (x^2-1)^n \mathrm dx = \frac{(-1)^2 4^{n+1} n! (n+1)!}{(2n+2)!}</math>.
}}
 
325

modifications